The key role for groundwater in urban water-supply security. Issue 10 (15th September 2022) - Foster, Stephen
Abstract: Groundwater provides nearly 50% of urban water supply, and probably a higher proportion at times of water stress. Groundwater systems generally exhibit exceptional resilience to drought and are well positioned to enhance water security for a wide range of users, provided they are adequately managed and protected to play the role sustainably. The serious urban water-supply crises of recent years, such as those experienced by Cape Town, Săo Paulo, and Chennai, have highlighted the vulnerability of major cities to surface water drought and a failure to incorporate groundwater as a key element to enhance water-supply security. But some progress has been made worldwide in adaptive sustainable management of groundwater for urban water supply, and this is illustrated by the cases of Hamburg, Lima, and Bangkok. HIGHLIGHTS: Role of groundwater in urban water supply. Public municipal versus private self-supply issues. Assessment of recent urban water-supply crises. Strengthening urban groundwater management. Profiles of water-supply status of key cities.